Tumour Microenvironment Stress Promotes the Development of Drug Resistance - Nicole A. Seebacher; Maria Krchniakova; Alexandra E. Stacy; Jan Skoda; Patric J. Jansson (MDPI AG, 2021)
Multi-drug resistance (MDR) is a leading cause of cancer-related death, and it continues to be a major barrier to cancer treatment. The tumour microenvironment (TME) has proven to play an essential role in not only cancer progression and metastasis, but also the development of resistance to chemotherapy. Despite the significant advances in the efficacy of anti-cancer therapies, the development of drug resistance remains a major impediment to therapeutic success. This review highlights the interplay between various factors within the TME that collectively initiate or propagate MDR. The key TME-mediated mechanisms of MDR regulation that will be discussed herein include (1) altered metabolic processing and the reactive oxygen species (ROS)-hypoxia inducible factor (HIF) axis; (2) changes in stromal cells; (3) increased cancer cell survival via autophagy and failure of apoptosis; (4) altered drug delivery, uptake, or efflux and (5) the induction of a cancer stem cell (CSC) phenotype. The review also discusses thought-provoking ideas that may assist in overcoming the TME-induced MDR. We conclude that stressors from the TME and exposure to chemotherapeutic agents are strongly linked to the development of MDR in cancer cells. Therefore, there remains a vast area for potential research to further elicit the interplay between factors existing both within and outside the TME. Elucidating the mechanisms within this network is essential for developing new therapeutic strategies that are less prone to failure due to the development of resistance in cancer cells.